2015
DOI: 10.1071/wr15080
|View full text |Cite
|
Sign up to set email alerts
|

Intense predation of non-colonial, ground-nesting bird eggs by corvid and mammalian predators

Abstract: Context Loss of eggs to predators is a major cause of reproductive failure among birds. It is especially pronounced among ground-nesting birds because their eggs are accessible to a wide range of predators. Few studies document the main causes of clutch fate of ground-nesting birds. Aims The main objective of the present study was to identify the major egg predator of red-capped plovers (Charadrius ruficapillus). We also investigated the effectiveness of the following two primary strategies available to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 60 publications
1
36
4
1
Order By: Relevance
“…In particular, corvids are considered a major threat to breeding shorebirds in the study area (Ekanayake et al . ), have resulted in interventionist management to conserve their avian prey (Tan et al . ), and evidently used the perching resources provided by boxthorn (this study).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, corvids are considered a major threat to breeding shorebirds in the study area (Ekanayake et al . ), have resulted in interventionist management to conserve their avian prey (Tan et al . ), and evidently used the perching resources provided by boxthorn (this study).…”
Section: Discussionmentioning
confidence: 99%
“…La perte d'oeufs causée par les prédateurs est particulièrement prononcée chez les oiseaux nichant dans le sous-bois comme les bulbuls parce que leurs oeufs sont accessibles à un large éventail de prédateurs (Ekanayake et al, 2015;Bellamy et al, 2017). L'évaluation de l'influence des types d'habitat et de l'influence du gradient croissant de destruction des forêts sur le taux de prédation des nids a toujours été un travail très compliqué à cause des difficultés à découvrir et à suivre les nids dans les forêts tropicales (Tewksbury et al, 2006;Newmark et Stanley, 2011).…”
Section: Introductionunclassified
“…Generalist predators (mostly birds and small mammals) have often been implicated in high egg depredation rates (Martin & Joron 2003;Wegge et al 2012;Ruffell et al 2014), with generalist avian species such as ravens and crows being common egg predators (Gardner 1998;Marzluff et al 2007;Ekanayake et al 2015). The dominant, most connected landscape feature surrounding woodland habitats can influence egg predator distribution (Debus 2006;Robertson et al 2014) with greater abundance of habitat generalist predators observed in woodland patches close to agricultural lands and irrigated land-use (Robertson et al 2014).…”
mentioning
confidence: 99%